COMMUNITY EDUCATION ON THE UTILIZATION OF HEALTHY LATRINES IN GUNONG MENASAH VILLAGE, SETIA BAKTI SUBDISTRICT, ACEH JAYA REGENCY - Lensoni, Lensoni; Yusoh, Anas (Transpublika Publisher, 2024)
This research discusses a community engagement initiative conducted in Gunong Menasah Village, Setia Bakti Sub-district, Aceh Jaya Regency, in the year 2023, focusing on the influence of lifestyle and family attitudes on toilet management. Employing a participatory education approach, the study aimed to enhance awareness and induce behavioral changes regarding sanitation. The research findings reveal a significant improvement in the community's understanding of proper sanitation practices, particularly concerning lifestyle choices and family roles. This positive shift is evident in the adoption of healthier sanitation practices and the construction of environmentally friendly toilets. However, challenges related to infrastructure and resources persist. Therefore, recommendations include sustaining sanitation facilities, continuing educational activities, enhancing collaboration with relevant stakeholders, and conducting further research. This research contributes to practical insights and the implementation of sanitation programs at the community level.